COMPARATIVE EFFICIENCY MEASUREMENT OF THE SELECTED GARMENTS FACTORIES IN BANGLADESH: AN APPLICATION OF DATA ENVELOPMENT ANALYSIS (DEA) - Hossain, Hamayet; Rahman, Md. Mizanoor; Huda, Md. Nazmul; Sabur, Md. Abdus (International Journal of Research -GRANTHAALAYAH, 2023)
Readymade garments sector is the largest export earning sectors in Bangladesh. The efficiency of that sector is needed to compete and survive in the competitive global market. For the purpose of identifying the inputs and output variables which are deriving the efficiency of garments factories in Bangladesh, five garment factories have been selected purposively on the basis of availability of data as a sample size. Pearson coefficient correlation has been used to find out significant input variables related with output variable of sales revenue indicating the result that only cost of material and labour has significant impact among four input variables. From the method of CRS input oriented DEA, it is estimated that two garments factory are efficient relative to the(Fawellient factory of the rest three. If it is possible to reduce the excessive used of inputs (percentages) cost of material and labour then rest three inefficient factories would be capable as like as efficient two.